Adult education as political participation - Ian Baptiste (Adult Education Research Conference, 1994)
Most adult education programs are wedded to human capital theory, a theory which ignores structural barriers to social equality such as sexism, racism, and classism. Proposed is an alternative, which, in addition to dispensing human capital (marketable skills), seeks to provide opportunities for students to hone the tools needed to overcome the impediments to social equality. I call this type of education: education as political participation.